UNDERDIAGNOSED CLASSICAL PRIMARY HYPERPARATHYROIDISM AND RAPID PROGRESSIVE DEMENTIA: CASE REPORT AND LITERATURE REVIEW - Pirapattanapong, Jiranon; Thanyawan, Karnwara (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 76-year-old female presented with forgetfulness anddisorganized behavior 3 months prior to admission. She had hypertension and also had postmenopausal osteoporosis which was treated with oral alendronate plus vitamin D for 7 months. After complete metabolic panels, laboratory results revealed unexpected serum calcium 16-19 November 2023 Bangkok, Thailand Poster Presentations 49 15.0 mg/dL, ionized calcium 8 mmol/L, phosphorus 2.77 mg/dL, intact parathyroid hormone 415 pg/mL, 25 (OH) D 55.3 ng/mL, ALP 145 U/L, and eGFR 33.3 mL/min. On physical examination, all were unremarkable except for mild dehydration. Her Thai mini-mental state examination score (TMSE) was 11/30 which was compatible with mild cognitive impairment. After saline infusion, her TMSE score improved, and serum calcium gradually decreased to less than 12.0 mg/dL. A Sestamibi scan revealed a single parathyroid adenoma. Alendronate was continued due to the very high risk of osteoporotic fracture. In this case, we demonstrated a PHPT patient who presented with rapid progressive dementia which was one of the neuropsychiatric manifestations, similarly shown in other series.